Product quality control analysis using the six sigma method - Ridwan, Asep; Sonda, Atia; Amelia, Amelia (Universitas Sultan Ageng Tirtayasa, 2023)
Technological improvements and developments have significantly altered consumers' perceptions of product quality. The production of high-quality products is only possible through a robust manufacturing process. However, during the production process, various issues may arise, leading to the production of defective products. As a result, manufacturing companies like XYZ are now required to conduct product quality control to minimize the number of defects. The objective of this study is to control product quality by reducing defects at XYZ. To achieve this, we have employed the Six Sigma method, which involves several stages, such as define, measure, analyze, improve, and control. Our research indicates that product A is prone to defects, with density being the most common type. We have calculated the DPMO (defects per million opportunities) to be 2580.66, while the sigma value is 4.297. The process capacity that produces problems at XYZ is at an average level for US industry. Additionally, we have used the 5W + 1H approach to propose improvements during the Improve stage. However, our recommendation for enhancing the production process to reduce defects is still a work in progress and needs to be executed, assessed, and monitored to reach world-class industry standards.